Global evidence directing regional preventive strategies in Southeast Asia for fighting TB/HIV - Myo Nyein Aung; Saiyud Moolphate; Damodar Paudel; Mangalasiri Jayathunge PH; Duangjai Duangrithi; Kinley Wangdi; Thin Nyein Nyein Aung; Thaworn Lorga; Kazue Higuchi (Journal of Infection in Developing Countries)
Tuberculosis (TB) and human immunodeficiency virus (HIV) co-epidemics form a huge burden of disease in the Southeast Asia region. Five out of eleven nations in this region are high TB/HIV burden countries: Myanmar, Thailand, India, Indonesia and Nepal. The trends of TB incidence in these countries have been rising in recent years, in contrast to a falling global trend. Experts in the field of TB control and health service providers have been perplexed by the association of TB and HIV infections which causes a mosaic clinical presentation, a unique course with poor treatment outcomes including death. We conducted a review of contemporary evidence relating to TB/HIV control with the aims of assisting integrated health system responses in Southeast Asia and demystifying current evidence to facilitate translating it into practice.